Spatial Evacuation Analysis Based on Mount Kaba Volcano, Bengkulu Indonesia Disaster Mitigation Eruption - Memo Memito; Lia Hasmita; Cipta Estri Sekarrini; Dedi Hermon; Iswandi Umar; Aprizon Putra (Pascasarjana, Universitas Negeri Padang, 2020)
This study aims to analyze the zoning of the eruption hazard, the area of ​​land affected, and the determination of the evacuation route based on the eruption mitigation of the Mount Kaba Volcano. This study uses the interpolation method and maximum likelihood for determining the type of land use and the network analyst approach for determining the distance of the effective evacuation route. The zoning for the Mount Kaba Volcano eruption in Selupu Rejang and Sindang Kelingi Districts can be divided into 4 zonings. The first is the forbidden zone (0-3km) with an affected area of ​​1,431.37 ha. The second hazard zone I (3-5 km) with an affected area of ​​1,300.28 ha. The three danger zones II (5-7 km) with an affected area of ​​1,464.78 ha, and the four moderate danger zones (7-10 km) with a land area of ​​1,045.2 ha which has the potential to be affected by the eruption of Mount Kaba Volcano. The land uses consist of 1803 ha of forest, 2895.3 ha of gardens, 186.3 ha of fields, 213.95 ha of shrubs, and 143 ha of settlements. The evacuation route for the Mount Kaba Volcano eruption disaster can be divided into 3 routes. First evacuation route I with a length of 7.98 km, evacuation route II with a length of 11.89 km, and evacuation route III with a length of 5.8 km which can be utilized by the community in mitigating volcanic eruptions.